The Effect of Product Quality, Customer Satisfaction, Trust, and Brand Image on Interest To Repurchase Kanzler Frozen Food Products - Mochammad Wafie Arsyad; Ahmad Cik; Adam Nurkholik; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
Research with the aim of analyzing the influence of product quality factors, consumer satisfaction, trust and brand image on repurchase intention on Kanzler Frozen Food products. In quantitative research with primary data from the results of distributing questionnaires to respondents as many as 100 consumers. Using descriptive analysis method and inferential analysis by conducting tests namely instrument test analysis, feasibility test of multiple linear regression correlation analysis models and hypothesis testing. The results of the regression analysis showed that there was a positive influence on repurchase intention based on the results obtained in the regression equation model Y = 0.624 (X1) + 0.162 (X2) + 0.181 (X3) + 0.230 (X4). The due diligence interpretation stated that the model in this study passed the due diligence based on a significance value obtained of 0.000 in the ANOVA table, this means that all independent variables have a significant effect on repurchase intention. The results of the hypothesis testing in this study are based on the acquisition of a significance value for the product quality variable of 0.000, then the satisfaction variable of 0.014. Then the trust variable is 0.007 and the brand image variable is 0.001. So it was concluded that the hypothesis in this research was proven to be accepted based on the significance value obtained. The producers of Kanzler Frozen Food are advised on the Product Quality factor which has the greatest contribution value in terms of influence on consumer repurchase interest, paying more attention to consumer needs and desires in order to increase consumer repurchase interest